POMDP planning for the creation of service packages - Ferrarini Oliver, Cintia (2014)
The generation of complex systems where the user requires decisions based on several criteria involves building a relationship of global preference for a set of alternatives evaluated. Between these systems there are the Tourist Systems, that was impulse by internet like a facilitator in the access of different sources of information for travel planning. Currently, tourists should not only visit multiple independent Web sites (airlines, hotels, etc.) and await a considerable time receiving confirmation responses. All these actions required generating a stochastic system that can meet the services and generate plans. Are being studied POMDP algorithms, in order to obtain a method for packages tailored to user requirements. Under the hypothetical-deductive methodology, this includes the study of service pakage´s composition, application, comparison and validation by a computer prototype with real users for a Web Recommender System. This thesis is framed within a PICT project called "E-OASIS Integrated Travel Services to facilitate easy access to Local Cultural Heritage" whose technical objective is to develop a Customized Recommender System for Tourist Services in the Province of San Juan. The automatic planning in real world problems has become a subject of interest to the scientific community because it allows computationally establish courses of action in cases where a human cannot addressed adequately for the complexity. The motivation for this work focuses on two aspects of the automatic planning, the scientific contributions and its practice application. (Párrafo extraído del texto a modo de resumen)